Better Together - Sposato, Jonathan (Ascent Audio, 2018)
Better Together provides powerful and implementable solutions to fostering gender equality in your business. As a result, your business will be more successful, your customers will be happier with better products/services, and your employees will be much more fulfilled. Women are one half of our species and over half of the earth's population. There is no product or service women don't buy. And yet, today only twenty-four women CEOs lead America's Fortune 500 companies. If you survey the landscape of founders who've created the most successful companies of recent years, you will mostly find white males. Zuckerberg, Dorsey, Cheskey, Kalanick, Evan Spiegel-captains of Facebook, Twitter, Airbnb, Snapchat-revolutionary founders who have created massively valuable companies impacting billions. Does this mean that women don't have great ideas, that women don't build and lead great companies? The goal of Better Together is to provide managers, employees, CEOs, and board members a guide to build a sustainable robust female workforce at all levels.